Mechanical Properties of Large-Volume Waste Concrete Lumps Cemented by Desert Mortar: Laboratory Tests - Hui Chen; Zhiyuan Qi; Baiyun Yu; Xinyu Li (Buildings)
In response to the high cost and environmental impact of backfill materials in Xinjiang mines, an eco-friendly, large-volume composite was developed by bonding desert-sand mortar to waste concrete. A rock-filled concrete process produced a highly flowable mortar from desert sand, cement, and fly ash. Waste concrete blocks served as coarse aggregate. Specimens were cured for 28 days, then subjected to uniaxial compression tests on a mining rock-mechanics system using water-to-binder ratios of 0.30, 0.35, and 0.40 and aggregate sizes of 30–40 mm, 40–50 mm, and 50–60 mm. Mechanical performance—failure modes, stress–strain response, and related properties—was systematically evaluated. Crack propagation was tracked via digital image correlation (DIC) and acoustic emission (AE) techniques. Failure patterns indicated that the pure-mortar specimens exhibited classic brittle fractures with through-going cracks. Aggregate-containing specimens showed mixed-mode failure, with cracks flowing around aggregates and secondary branches forming non-through-going damage networks. Optimization identified a 0.30 water-to-binder ratio (Groups 3 and 6) as optimal, yielding an average strength of 25 MPa. Among the aggregate sizes, 40–50 mm (Group 7) performed best, with 22.58 MPa. The AE data revealed a three-stage evolution—linear-elastic, nonlinear crack growth, and critical failure—with signal density positively correlating to fracture energy. DIC maps showed unidirectional energy release in pure-mortar specimens, whereas aggregate-containing specimens displayed chaotic energy patterns. This confirms that aggregates alter stress fields at crack tips and redirect energy-dissipation paths, shifting failure from single-crack propagation to a multi-scale damage network. These results provide a theoretical basis and technical support for the resource-efficient use of mining waste and advance green backfill technology, thereby contributing to the sustainable development of mining operations.